40.2: Integrated Solution for Roll‐to‐Roll Fine Copper Circuit Touch Sensor Making. (28th November 2018) - Hsu, Ming-Ann; Lin, Chia-Hui; Igawa, Akihiko
Abstract : Applying common photolithography process to flexible substrate with novel formulated lithographic chemicals, flexible touch sensor film can be manufactured by roll‐to‐roll process. Extremely fine copper pattern (<2um) could be obtained without using fine mask pattern and with no copper damaging. With proprietary low temperature curing flexible black matrix photoresist to make the fringe, all layers of metal mesh touch sensor can be integrated onto one film substrate to achieve true flexible touch for flexible displays. This integrated solution is enabled by four new formulated materials: one low temperature curing black matrix photoresist for fringe, one flexible positive‐tone photoresist and one copper etchant for fine circuit patterning, and one low temperature curing clear photoresist for passivation.